Breast cancer growth and metastasis: interplay between cancer stem cells, embryonic signaling pathways and epithelial-to-mesenchymal transition - Takebe, Naoko (BioMed Central, 2011)
Induction of epithelial-to-mesenchymal transition (EMT) in cancer stem cells (CSCs) can occur as the result of embryonic pathway signaling. Activation of Hedgehog (Hh), Wnt, Notch, or transforming growth factor-β leads to the upregulation of a group of transcriptional factors that drive EMT. This process leads to the transformation of adhesive, non-mobile, epithelial-like tumor cells into cells with a mobile, invasive phenotype. CSCs and the EMT process are currently being investigated for the role they play in driving metastatic tumor formation in breast cancer. Both are very closely associated with embryonic signaling pathways that stimulate self-renewal properties of CSCs and EMT-inducing transcription factors. Understanding these mechanisms and embryonic signaling pathways may lead to new opportunities for developing therapeutic agents to help prevent metastasis in breast cancer. In this review, we examine embryonic signaling pathways, CSCs, and factors affecting EMT.